The Influence of Village Apparatus Competency, Village Treasurer's Tax Compliance, and Community Participation on Accountability of Village Fund Management in Tambak District, Gresik Regency - Qulub, Latifatul; Hidayat, Muhammad Taufiq (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2024)
This study aims to examine the impact of the competence of village apparatus, tax compliance of village treasurers and community participation on the accountability of village fund management, especially in villages in Tambak District, Gresik Regency. The method adopted in the following research is a quantitative method with a population of 13 villages in Tambak District, while the sample is 6 villages in Tambak District. The test utilizes the Statistical Product and Service Solution (SPSS 22) application with multiple linear regression analysis tests, t tests, f tests and determination tests (R). Research findings show that the competency of village aparatus does not have a significant positive impact on the accountability of village fund management, while the village treasurer's tax compliance and community participation have a significant positive impact on the accountability of village fund management.